"… und das Scharnier rostet weiter vor sich hin". - Kühl, Carsten (Berliner Wissenschafts-Verlag, 2021)
Das Kapitel widmet sich der vertikalen Verteilung der Umsatzsteuer in Deutschland und den Möglichkeiten der Reformierung des Verfahrens.

The vertical distribution ofthe sales tax is a central element of German fiscal federalism. Its mechanism has been rusty for years. The article asks if it should be reformed and how that could be done. One solution could be the introduction of an arbitration procedure.
... and the hinge continues to rust.
Keywords: Umsatzsteuer; Steuerverteilung; Föderalismus; Fiskalföderalismus